Legal Analysis of Trademark Rights Violations Against Business Logo Imitation from the Perspective of Fatwa MUI Number 1/MUNAS-VII/MUI/5/2005 (Study Between Mie Gacoan and Mie Kacoan) - Daulay, Nurhayati; Rokan, Mustapa Khamal (AL-IKTISAB: Journal of Islamic Economic Law, 2023)
The use of trademarks or logos is an important aspect in the business world that not only reflects the identity of the company but also constitutes a valuable asset that must be protected. However, currently many businesses or industries are committing violations in the use of trademarks or logos that are already owned by other businesses or industries. This research aims to analyze cases of logo or trademark imitation from the perspective of positive law and the perspective of Fatwa MUI. The research method used in this research is empirical juridical research. The result is, the use of Mie Kacoan brand was declared guilty of imitating the business logo that had similarities in essence with Mie Gacoan, due to the fulfillment of three criteria of similarity, namely in form (visual), pronunciation, and sound. Fatwa MUI Number 1/MUNAS-VII/MUI/5/2005 concerning Intellectual Property Rights (IPR) serves as a guideline for the protection of trademark rights in Islam. Which explains that any form of violation of Intellectual Property Rights (IPR), including but not limited to using, disclosing, creating, using, selling, importing, exporting, distributing, delivering, providing, announcing, reproducing, copying, counterfeiting, and pirating someone else's IPR without permission is considered oppression and is deemed haram. In addition to Fatwa MUI, trademark rights are also protected by Law Number 20 of 2016 concerning Trademarks and Geographical Indications.